Estimating the prevalence alcohol use disorder and relapse risks in Kermanshah Province of Iran: Integrating direct, indirect methods, and tree-based analysis - Faezeh Tatari; Mostafa Alikhani; Farnaz Radmehr; Sara Hookari; Mehran Kamani; Vahid Farnia; Omran Davarinejad; Mehdi Moradinazar; Lida Olfati; Narges Nazari Harmooshi; Safora Salemi; Bahareh Rahami (PLoS ONE, 2025)
Background Alcohol Use Disorder (AUD) is a major health issue in various societies, particularly in Iran, with detrimental consequences. In this study, we examined the prevalence of AUD using direct and indirect methods (Network Scale-Up model (NUS) and Crosswise model (CM)), as well as the factors associated with relapse, utilizing tree analysis. Methods In this cross-sectional study conducted among individuals aged 15–69 in Kermanshah Province, western Iran, 6,127 participants were selected using stratified sampling. Data collection was performed electronically and recorded in a digital system by trained interviewers. The indirect assessment utilized both NUS and CM methods and Factors affecting the recurrence of alcohol use were investigated using the tree regression method. Results The prevalence of AUD in western Iran was estimated at 3.20% using direct methods, 20.54% using the CM method, and 7.21% using the NUS method. A total of 34 (0.7%) individuals reported relapse in AUD. Tree analysis results indicated that the frequency of relapse (chi square = 4994.0, P < 0.001) and a history of physical illness in the family (chi square = 6.0, P = 0.031) were influential factors in alcohol relapse. Conclusion The findings of this study provide insights into the actual levels of AUD and factors associated with relapse, enabling healthcare providers to make better decisions for preventive planning to reduce AUD and improve treatment outcomes.